Best damn firewall book period - Behrens, Thorsten (Burlington, Mass. : Syngress, 2007)
The Second Edition of the Best Damn Firewall Book Period is completely revised and updated to include all of the most recent releases from Microsoft, Cisco, Juniper Network, SonicWALL, and Check Point. Compiled from the best of the Syngress firewall library and authored by product experts such as Dr. Tom Shinder on ISA Server, this volume is an indispensable addition to a serious networking professionals toolkit. Coverage includes migrating to ISA Server 2006, integrating Windows Firewall and Vista security into your enterprise, successfully integrating Voice over IP applications around firewalls, and analyzing security log files. Sections are organized by major vendor, and include hardware, software and VPN configurations for each product line. New to this Edition: * Microsoft firewall protection, from Windows Firewall to ISA Server 2006 * Cisco PIX Version 7, including VPN configuration and IDS * Analyzing Firewall Logs and Reports * VoIP and Firewall Bypassing.
Protecting Your Perimeter; NetScreen; SonicWall; Cisco PIX; ISA Server; Check Point; Linux; Open Source Firewalls; Personal Firewalls; Analyzing Logs; VoIP Bypassing.
Previous ed.: 2003.
Includes bibliographical references and index.
Keywords: Firewalls (Computer security); Electronic books